СИНДРОМ ХРОНИЧЕСКОЙ АБДОМИНАЛЬНОЙ ИШЕМИИ КАК ДИАГНОСТИЧЕСКАЯ ПРОБЛЕМА - Н. С. Безносов; Т. И. Шнурова; Т. Г. Корниенко; А. А. Калугин; Г. В. Виноходова; Н. С. Вотрина (SINAPS LLC, 2015)
We provide description of clinical case of chronic abdominal ischemia, which is usually associated with great variety of symptoms and low specificity. Such patients spend a lot of time for different specialists and different types of laboratory and instrumental analysis. Usually there are a lot of different diagnosis and different medication without real help and development of depression in patients. Article contains historical information, classification, information about diagnostic methods and treatment.